(untitled) (Research in Agriculture Livestock and Fisheries, 2022)
Nitrogen (N) management is important to assess the N effect on soil and plant under the organic farming system. With this in mind, a glasshouse experiment was conducted to determine the effect of various N inputs on selected soil chemical properties, nutrient content and yield of spinach (Amaranthus spp). The experimental treatments were focused on the different percentages of N input (2, 4 and 6% of N from organic sources) with soil alone as a control. The treatments were applied 14 days after seeding (14-DAS) at a recommended rate of 2 t/ha. The study result found that 4-6% of N input (with T3 and T4) had improved selected soil parameters such as pH, CEC, total N, available-P and exchangeable-Ca. Further, total N content in spinach (cultivated organically), as well as spinach yield, were significant. Study findings have shown that within 4% to 6% of N input promotes soil quality, total nutrients in spinach (leafy vegetables), and can be scaled up to farm level to sustain organic system productivity. Vol. 9, No. 2, August 2022: 135-144